2022
DOI: 10.3390/medsci10020033
|View full text |Cite
|
Sign up to set email alerts
|

Human Trial for the Effect of Plasma-Activated Water Spray on Vaginal Cleaning in Patients with Bacterial Vaginosis

Abstract: Underwater plasma discharge temporally produces several reactive radicals and/or free chlorine molecules in water, which is responsible for antimicrobial activity. Hence, it can simply sanitize tap water without disinfectant treatment. Additionally, the spraying technique using cleaning water exploits deep application in the narrow and curved vaginal tract of patients. Herein, we attempted a clinical trial to evaluate the vaginal cleaning effect of spraying plasma-activated water (PAW) to patients with vaginit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…In previous studies, we confirmed the bactericidal effect of PAWs on clinically abnormal vaginal microbiota in clinical practice [14,19,20]. Patients sprayed with PAW (22.3%) had fewer Gram-positive and -negative bacteria than betadine treatment (BT) patients (14.4%) [14]. A significant decrease after treatment was observed in the following pathogenic organisms: Mycoplasma hominis (30 ± 15.28% decrease), Ureaplasma urealyticum (25 ± 9.93% decrease), Ureaplasma parvum (23 ± 8.42% decrease), and Candida albicans (28 ± 10.86% decrease) [19].…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…In previous studies, we confirmed the bactericidal effect of PAWs on clinically abnormal vaginal microbiota in clinical practice [14,19,20]. Patients sprayed with PAW (22.3%) had fewer Gram-positive and -negative bacteria than betadine treatment (BT) patients (14.4%) [14]. A significant decrease after treatment was observed in the following pathogenic organisms: Mycoplasma hominis (30 ± 15.28% decrease), Ureaplasma urealyticum (25 ± 9.93% decrease), Ureaplasma parvum (23 ± 8.42% decrease), and Candida albicans (28 ± 10.86% decrease) [19].…”
Section: Introductionsupporting
confidence: 82%
“…In previous studies, we confirmed the bactericidal effect of PAWs on clinically abnormal vaginal microbiota in clinical practice [14,19,20]. Patients sprayed with PAW (22.3%) had fewer Gram-positive and -negative bacteria than betadine treatment (BT) patients (14.4%) [14].…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations